2007
DOI: 10.1148/radiol.2421051167
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos-induced and Smoking-related Disease: Apportioning Pulmonary Function Deficit by Using Thin-Section CT

Abstract: The proposed CT system provides a semiquantitative method for assessing the relative contribution of asbestos-induced pleuropulmonary disease and smoking-related emphysema to functional impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 25 publications
4
15
0
Order By: Relevance
“…These results are consistent with those from the current investigation in that DL CO values were particularly reduced at baseline, even when most of the other PFTs, including spiromtery, were within the limits of normality. A recent study by Copley et al [2007] illustrates the difficulty in quantifying the severity of asbestos-related lung disease by using PFTs in isolation. The authors found that combined HRCT variables predicted 57% of the variability in DL CO in 133 asbestos-exposed subjects, despite considerable variation in the proportion of coexisting pathologic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those from the current investigation in that DL CO values were particularly reduced at baseline, even when most of the other PFTs, including spiromtery, were within the limits of normality. A recent study by Copley et al [2007] illustrates the difficulty in quantifying the severity of asbestos-related lung disease by using PFTs in isolation. The authors found that combined HRCT variables predicted 57% of the variability in DL CO in 133 asbestos-exposed subjects, despite considerable variation in the proportion of coexisting pathologic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Such variation has been confirmed in other studies examining lung pattern type, with an interobserver variation of 81% (kappa of 0.48) and a similar intraobserver variation (kappa of 0.37 to 0.78) (7). Other visual scoring system have been suggested by Remy-Jardin et al (8) or Copley et al (9). However, in their studies, the reproducibility of the scoring systems was not assessed and their scoring systems were semi-quantitative methods.…”
Section: Introductionmentioning
confidence: 99%
“…Pairon et al reported that pleural plaques may be an independent risk factor for lung cancer and could be used as an additional criterion for lung cancer CT screening of high-risk population 2. In a study evaluating asbestos-induced CT findings by Copley et al , pleural plaques showed the best inter-reader agreement (κ=0.88) compared with other findings in the lungs such as traction bronchiectasis, parenchymal bands, coarseness of fibrosis, subpleural lines and interstitial lines 18. Therefore, identification of pleural abnormalities on CT may affect risk stratification and clinical management of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Minor pleural changes are defined as non-specific, slight, focal thickening or irregularities of the pleura that are identifiable on CT. Pleural plaques are defined as well-demarcated areas of pleural thickening, seen as elevated flat or nodular lesions that often contain calcification (figure 1). 17 Diffuse pleural thickening is defined as a continuous sheet of pleural thickening with tapering margins 18. The first reader reviewed all CT scans for the pleural abnormalities.…”
Section: Methodsmentioning
confidence: 99%